BOFUS and CLARITY: streamlining blockchain architecture and assessment for advanced standardization and interoperability in distributed ledger technologies - Saxena, A.; Chiu, Bang Han (Frontiers in Blockchain, 2023)
The Blockchain Organized Framework for Unified Systems (BOFUS) and the Comprehensive Ledger Assessment for Robust Interoperability and Trustworthiness (CLARITY) initiatives address the challenges of understanding, standardizing, and enabling interoperability between diverse blockchain systems. BOFUS is a comprehensive 5-layer model that systematically organizes core blockchain components, while the CLARITY assessment provides a standardized method for evaluating and comparing blockchains using the CONFIGURE acronym. Together, these initiatives aim to facilitate a deeper understanding of blockchain technology, promote effective communication and collaboration between stakeholders, and ultimately advance the development and adoption of distributed ledger technologies. This paper presents an in-depth discussion of the BOFUS architecture and the CLARITY assessment, exploring their utility in various blockchain scenarios and their potential implications for the future of blockchain technology.